SMART AUDIO AMPLIFIER - Zarate V, Josue; MuÃ±oz C, Enrique; Diaz C., Ruben (European Scientific Journal, ESJ, 2016)
This project focuses on the control of audio power amplifiers. Is the development and implementation of a system of controlled cooling and optimizing the power consumption and temperature generated, using an advanced control algorithm. The approach is based on the configurations of integrated circuits (IC) audio amplifiers allowing us to obtain data energy consumption and parameters of temperature gradient, generally with the required parameters will be processed by a microcontroller (uC) to pass to run programmed by a control algorithm(PID) instructions. The design of the electronic circuit is composed of passive and active electronic devices essentially controlled by protocol (I2C / TWI), Class-T Digital Audio Amplifier, sensors, microcontrollers working on master and slave protocol using UART mode. Configurations and analysis by module (ADC), including a turning on system and automatic shutdown and peripherals, the frequency at which works is 20Hz to 20kHz with 75dB decibel maximum. Finally both analysis and theoretical control simulation showed that the use of a good control configuration based on energy regulation and switching amplifiers allows the temperature was controlling with excellent accuracy and reduces wear on stage of electronic circuit.